Pelatihan Penyusunan Modul Ajar Pembelajaran Inovatif untuk Mengembangkan Profesi Pendidik di Sekolah Dasar - Wijayanti, Kristina; Waluya, St Budi; Sukestiyarno; Kartono; Putriaji Hendikawati (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Teaching modules are one of the important educational tools that support the success of the learning process. This training and mentoring activity is conducted with the aim of providing knowledge and equipping elementary school educators to be able to develop Innovative Learning Teaching Modules. The mentoring and training activities for the preparation of innovative learning teaching modules were conducted at Kebon Dalem Elementary School in Semarang and were attended by 32 teachers. The activities were carried out in the form of training and mentoring divided into two stages. The first stage uses lecture, demonstration, and question-and-answer methods. In the second stage, assignments were given and the results of the teaching module products were presented. This activity provides a lot for the participating teachers because, in addition to imparting knowledge about innovative learning modules, it also offers assistance in the preparation of teaching modules for the teachers of Kebon Dalem Elementary School Semarang. The teaching module products generated in this activity can subsequently serve as a resource for teachers to carry out follow-up actions such as conducting classroom action research. The teachers hope that similar training activities can be conducted periodically and continuously, addressing topics relevant to the professional development of educators in elementary schools.